Brilliant Green Dye Elimination from Water Using Psidium guajava Leaves and Solanum tuberosum Peels as Adsorbents in Environmentally Benign Way - Rabia Rehman; Tariq Mahmud; Maria Irum (Journal of Chemistry)
The aim of this study is to check the feasibility of Psidium guajava (Guava) leaves and peels of Solanum tuberosum (Potato) as biosorbents in removal of Brilliant Green (BG) in batch mode. Surface analysis of biosorbents was done by FT-IR and quantitatively analyzed by Boehm titration. The removal of dye was confirmed by UV-VIS spectroscopy. Isothermal modeling was studied by using Langmuir, Freundlich, and Temkin isotherms. Various isothermal parameters for adsorption of Brilliant Green such as qm=1.075 mg/g, 1.173 mg/g ΔG°=-3.397, and −2.397 KJ/mol were noted for Solanum tuberosum peels (PP) and Psidium guajava leaves (GL), respectively. Similarly pH, moisture content, and various metals were quantitatively analyzed. Results showed that leaves of Psidium guajava were more effective for removal of Brilliant Green.